Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Hydrofoil performance optimization based on the Kriging method - Qiaowen Yu; Shigang Wang; Rui Deng; Dapeng Jiang; Bing Zheng; Suzhen Zeng (Ocean Engineering, 2025)

A new risk for the recovered Tibetan antelope (Pantholops hodgsonii): Co-exposure of microplastics with organophosphates in their habitats - Rui Guo; Caian He; Jian Sun; Shaohua Li; Chuntao Zhao; Zhiyong Ling; Liang Chen; Wenrui Zhang; Jingmeng Li; Bing Wang; Jufang Hu; Dongmei Yu; et al. (Journal of Hazardous Materials, 2025)

Screening and characterization of marine cyanobacteria for dairy farm wastewater treatment: Nodosilinea sp. E11 as a promising candidate for phycoremediation - Meiqi Zhang; Rui Xin; Yu Wang; Keqiang Zhang (Journal of Cleaner Production, 2025)

Retention-driven water flow regulation: A network perspective - Xuan Jiang; Jinsong Zhao; Zhiwen Cai; Jiating Li; Jian Wang; Ling Wang; Xiao Li; Rui Hao; Shuxia Yu; Zhihua Shi (Journal of Environmental Management, 2025)

Defect-driven bifunctional Cu/N co-doped biochar for synchronized adsorption and instant catalysis in organic pollutant degradation - Rui Yu; Fang He; Jingjing Wang; Zaiwen Jia; Chao Liu; Haihong Zhou (Journal of Environmental Management, 2025)

Single-atom Pt-engineered TiO₂ photoanode enabling low-charge voltage and high-efficiency neutral Zn-air batteries via photoelectrochemical enhancement - Wenliang Wang; JiangYuan Qiu; Tao Yu; Shuming Zhang; Xingwang Niu; Rui Guo; Jinsheng Li; Xuanwen Liu (Journal of Environmental Chemical Engineering, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Effect of combined treatment of pH-shifting and mild heating on gel properties of transglutaminase induced cold-set peanut protein isolate gel - Jing Chen; Si Qiu; Rui Li; Zining Fan; Yu Wang; Yuntao Wang (Food Research International, 2025)

DoLPHiN: a proposed architecture and technical implementation of a database of structural and functional properties of natural polysaccharides with health benefits - Yefu Xin; Yongling Cao; Shuheng Yang; Junhao Hu; Miao Tian; Jian Dai; Jing Shi; Bingcong Yu; Nike Gu; Xiangxu Hu; Rui Zhu; Qianni Duan; et al. (Food Chemistry, 2025)

Facile synthesis of cationic polymer networks with ultrahigh charge density for effective capture of ReO4− (surrogate of radioactive 99TcO4−) - Minsi Shi; Dingyang Chen; Zixu Ren; Chaofan Wang; Yu Yu; Guangli Yu; Rui Zhao (Environmental Research, 2025)

One polymer–multiple functions: Waterborne dual dynamic polyacrylate networks for self-healing and recyclable adhesives and coatings - Yu Chen; Wang Li; Rui Pu; Fengbiao Chen; Yujun Cheng; Yao Liu; Dong Luo; Siyu Nie; Xuelang Gao; Liang Shen; Fei Gao (Chemical Engineering Journal, 2025)

Trace polymer additive-mediated H-bond reconstruction and water-deficient Helmholtz layer for 4500 h Zn anodes - Huijie Li; Zichun Yuan; Leyao Li; Qiang Yu; Fuxin Wang; Rui Li; Yanxia Yu; Dezhou Zheng; Xihong Lu (Chemical Engineering Journal, 2025)

Dual pH/glutathione-responsive polyphenol-based self-assembled nanoparticles loaded with lambda-cyhalothrin show enhanced UV stability and non-target organism safety - Lei Wang; Zheng Zhang; Yu Fang; Rui Zhao; Shouhe Pan; Meng Yu; Yinjie Ma; Yinmin Wang; Xiquan Ding; Xinyu Guo; Fengyu Li; Pengkun Yan; et al. (Chemical Engineering Journal, 2025)

Start-up and operational strategies for side-stream nitrification reactors in a cyclic up-concentration nitrogen recovery process: Enhancing targeted nitrate conversion and deciphering nitrogen metabolism - Molin Lian; Zihang Ma; Guang Chen; Xiangdong Xu; Rui Tang; Shikun Yan; Yu Wang; Yuyue Zhang; Zhen Zhou (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

High-yield synthesis of biomass-derived carbon dots for enhanced taraxacum growth - Guanxiong Liu; Hui Wang; Jiaxin Dong; Yinying He; Rui Wang; Xiangli Li; Dongyue Liu; Jing Duan; Jing Feng; Xiaoyu Lu; Lijuan Gui; Sheng Hou; et al. (Biomass and Bioenergy, 2025)

Comparative analysis of sexual dimorphism in ultrastructure of sensilla on antennae, frons, and compound eyes of Azpeytia shirakii Hurkmans (Diptera: Syrphidae) - Bin Mao; Yu-Hui Cong; Ming-Hui Wang; Han-Rui Ren; Yun-Li Xiao (Zoomorphology, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Temporal transcriptomics reveal crucial networks underlying jasmonate-mediated diurnal floret opening and closure in rice - Rui Zhang; Xiaohui Xi; Xiaozhou Hu; Dan Xiang; Yi Wang; Yu Pan; Xi He; Yuhan Zhang; Lilan Hong; Yuanzhu Yang; Ming Zhou (Science China Life Sciences, 2025)

Water use strategies of Platycladus orientalis under diverse water management approaches in the western Loess Plateau: Insights from stable isotope analysis - Yu Zhang; Mingjun Zhang; Yuquan Qiang; Rui Lu; Cunwei Che; Shengjie Wang (Plant and Soil, 2025)

Metabolomics Reveals Reasons for the Efficacy of Acupuncture in Migraine Patients: The Role of Anaerobic Glycolysis and Mitochondrial Citrate in Migraine Relief - Zishan Gao; Xianzhong Yan; Rui Wang-Sattler; Marcela Covic; Guang Yu; Feifei Ge; Jia Lin; Qin Chen; Juan Liu; Sapna Sharma; Sophie Molnos; Brigitte Kuehnel; et al. (Phenomics, 2025)
Acupuncture is used worldwide to treat migraine, but its scientific mechanism remains unclear. Here, we report a 1 H NMR metabolomics study involving 40 migraine patients and 10 healthy individuals randomly receiving acupuncture or sham acupuncture, followed by machine learning techniques and functional analysis. We found that acupuncture at acupoints particularly enhanced anaerobic glycolysis and modified mitochondrial function by adjusting the levels of plasma pyruvic acid ( p = 0.012), lactic acid ( p = 0.031) and citrate ( p = 0.00079) at a Bonferroni-corrected level of significance compared to the pre-treatment level of these three metabolites in migraine patients. Therefore, acupuncture supplies energy to migraine patients and relieves migraine attacks. In contrast, we observed that sham acupuncture may partially supply energy to migraine patients through lipid metabolism by changing the levels of plasma lipid ( p = 0.0012), glycerine ( p = 0.021), and pyruvic acid ( p = 0.047) at a Bonferroni-corrected level of significance. The functional network analysis further indicates this different way of supplying energy contributes to the different effects of acupuncture and sham acupuncture. Our findings reveal novel metabolic evidence for the specific effect of acupuncture in relation to sham acupuncture. This metabolic evidence could enlighten a brand new direction into acupuncture analgesia mechanism, which in turn would pose fresh challenges for future acupuncture research.

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Peroxisome proliferator-activated receptor gamma prevents activation of RBL-2H3 cells by inhibiting FcεRI-mediated signal transduction - Yu Zhang; Suyu Ruan; Yuhang Xie; Xiaoqing Rui; Jianjun Zhou; Weihua Wang (Inflammation Research, 2025)

FAM72A promotes cervical cancer progression by regulating the PI3K pathway - Qin wang; Hao Yu; Rui Huang (Functional & Integrative Genomics, 2025)

Interpretable liquefaction prediction model based on stacking algorithm - Xiao Long; Rui Sun; Tong Zheng; Yu Wang; Zhaocheng Zhong (Earth Science Informatics, 2025)

Wheat straw incorporation and nitrogen fertilization increase antibiotic resistance gene abundance and dissemination potential in agricultural soil - Feng-Hua Wang; Rui-Ao Ma; Zi-Teng Liu; Xin-Di Zhao; Ruibo Sun; Wenxu Dong; Yuming Zhang; Min Qiao; Si-Yu Zhang (Soil Ecology Letters, 2025)

Research on Environmental Response Characteristic of Super-Long Inclined Shaft Tunnel and CO Diffusion and Ventilation Optimization of Blasting Procedures - Kong-fei Yu; Huai-bing Wang; Hong-yan Wang; Chen-qi Fan; Bu-rui Liu; Xuan-ke Ren (Applied Geophysics, 2025)

Two undescribed constituents from Salvia castanea Diels and evaluation of their cytotoxic activity - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Tashi Tsering; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Evaluation of efficacy of intensity measures for fast and reliable seismic fragility analysis of bridge columns - Jian-Cheng Dai; Dong-Sheng Wang; Xiao-Yu Chen; Wei-Jian Tang; Rui Zhang; Ying-Xin Hui (Soil Dynamics and Earthquake Engineering, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Enhancing NO3− reduction on BiFeO3/Cu cathode via ferroelectric polarization: A novel strategy for surface electronic structure regulation - Hao Chen; Houfen Li; Yue Zhao; Yunlong Ma; Zhichao Liu; Rui Li; Sufang Wang; Aijuan Zhou; Xiuping Yue; Haibing Meng; Hongtao Yu; Xu Zhao (Journal of Environmental Management, 2025)

Development of fluorescent artificial receptors for specific recognition and rapid detection of Escherichia coli O157:H7 - Qianjin Li; Rui Li; Mengdi Wang; Jinjin Wang; Tingting Wang; Yu Jin; Jianlin Li; Fenying Wang (Food Chemistry, 2025)

The effect of microplastic pollution on rice growth, paddy soil properties, and greenhouse gas emissions: A global meta-analysis - Shi-Wen Deng; Wei Liang; Hong-Yu Chen; Mutaz Mohammed Abdallah; Rui-Long Wang (Environmental Research, 2025)

Fe3+ modulated protein-based soft actuators for organic solvent working conditions: Spatiotemporal programmability, multi-terrain locomotion, self-sensing and full biodegradability - Shaorong Zong; Xiaohui Chu; Jia Kang; Cungang Gao; Pengxin Jia; Yue Sun; Ming Zhang; Kaiming Wang; Rui Nian; Wenfa Yu (Chemical Engineering Journal, 2025)

Stable and high-capacity MnO2-organic aqueous “rocking chair” battery - Runmo Wang; Yu Zhang; Rui Yang; Yaqun Wang; Ze Yang (Chemical Engineering Journal, 2025)

Phytic acid and melamine-modified microcrystalline cellulose as effective flame retardants in polylactic acid composites - Rui Pan; Erlei Yu; Yijing Wang; Guowei Liu; Zhong Wei (Carbohydrate Polymers, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Phosphorylation of a conserved TBXT threonine residue is vital to vertebral development - Shuxia Chen; Chennan Liu; Ying Zhao; Lingbo Wang; Rui Peng; Lei Lu; Qian Yu; Yichen Jin; Jinsong Li; Xueyan Yang; Yunping Lei; Hongyan Wang (Science China Life Sciences, 2025)

Association between ophthalmology clinic visit for dry eye disease and environmental nitrogen dioxide exposure: a time-series study - Yiming Wang; Mengyu Wu; Rui Wang; Shoupeng Li; Aihua Yu (Environmental Geochemistry and Health, 2025)

Enhanced rice phosphorus use efficiency under elevated atmospheric CO2 and its drivers - Haiwei Zhang; Ting Xiao; Zihua Shi; Rui Ren; Yu Jiang; Yanfeng Ding; Songhan Wang (Agriculture, Ecosystems & Environment, 2025)

A new flex power detection method for BDS-2 - Yu Lu; Nanshan Zheng; Xuexi Liu; Ahao Wang; Shouqing Zhu; Rui Ding; Zinuo Wang (Advances in Space Research, 2025)

YOLOv11-OPNet: dual-modality framework for fishing vessel detection in complex long-range maritime scenarios - Jian Li; Hong Yu; Rui Shi; Zhibo Cui; Hongjing Dai; Zijian Wu; Yue Wang (Aquaculture International, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Characteristics and primary controls of coral reef carbonate karstification in the South China Sea since the Miocene - Yang Yang; Kefu Yu; Bin Xiong; Wei Jiang; Shendong Xu; Rui Wang; Tianlai Fan (Frontiers in Marine Science, 2025)
Coral reef karstification plays a vital role in sea-air CO 2 exchange, yet its mechanisms remain unclear. This study employs an 878.22-m coral reef sequence (dating to19.6 Ma) from Well CK2 in the Xisha Islands, South China Sea (SCS), to investigate karstification processes, including their signatures, primary controls, and implications for marine carbonate dissolution in global carbon cycling. Petrological and geochemical analyses of CK2 revel distinct karstification characteristics, including: (1) higher surface porosity 25–30%), with randomly distributed pores and fractures of variable sizes and shapes; (2) yellowish-brown to black impregnations; (3) micritic cements accompanied by well-crystallized mineral crystals, and (4) moderately well-sorted and rounded grains. Geochemical signatures show elevated 8787 Sr/ 86 Sr, Mn content, and Mn/Sr ratios, coupled with depleted δ¹³C, δ 18 O and Sr content. These features collectively indicate that karstification in CK2 was dominated by non-selective dissolution and recrystallization processes, principally occurring at the mixing zone in meteoric water systems during prolonged subaerial exposure. Karstification signatures varied across geological epochs, implying different controlling mechanisms. Late Miocene (12.6–10.2 Ma), driven by sustained sea-level fall, exhibited an extreme 87 Sr/ 86 Sr shift and severe erosion. Pleistocene (2.2–1.8, 1.1–0.89, 0.29 and 0.2 Ma), influenced by frequent sea-level fluctuations and warm, humid environments linked to glacial-interglacial cycle and Asian monsoon, displayed the highest surface porosity (15–40%, mean 25%), ochre to tawny impregnations, and micritized cements, along with negative δ¹³C-δ 18 O and elevated 87 Sr/ 86 Sr and Mn/Sr ratios. In contrast, the Middle Miocene Climatic Optimum (16.6–16 Ma) lacked typical karst characteristics but comprised of well-rounded and sorted coral gravels, suggesting reef-building organisms mediate karstification via substrate architecture. These findings demonstrate that sea-level changes and climate conditions control coral reef karstification intensity. Concurrently, dissolution during karstification may significantly modify ocean alkalinity and dissolved inorganic carbon, with potential feedback on carbon cycling in future climate scenarios.

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Vivianite@interstitial-carbon doped MoS2-induced peroxymonosulfate activation for norfloxacin removal: Performance, mechanism and regeneration - Fang He; Jingjing Wang; Jieru Fang; Rui Yu; Zaiwen Jia; Haihong Zhou (Journal of Environmental Chemical Engineering, 2025)

Research progress and prospects of MOF-based and -derived cathode catalysts in microbial electrochemical technologies: Mechanisms, performance and applications in wastewater treatment - Zhen Liu; Rui Li; Qin Qi; Xiaomin Chen; Jiale Yu; Renjun Wang; Junfeng Chen (Journal of Environmental Chemical Engineering, 2025)

Enhanced moisture tolerance and toluene oxidation activity of δ-MnO2 catalysts by Sn doping: Phase transition and surface protection - Yiming Li; Mengxia Xu; Rui Liu; Shuibo Wang; Taotao Sun; Zijun Yan; Cong Wan; Hongbo Yu; Haocheng Li; Haotian Li; Xudong Zhao; Kaijie Li; et al. (Fuel, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Bioinspired conductive-catalytic network accelerates rate-determining steps at cathode-electrolyte interface for high-loading Li-S batteries - Cai-Yun Zhang; Chen-Yang Wang; En-Zhu Zhao; Guowei Yu; Hui-Ling Deng; Rui Huang; Zhao-Yun Wang; Pu Hu; Min Yan; Zhitian Liu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Tailoring sponge-like nitrogen-enriched biochar: A green and sustainable remediation technology for Pb and Cu contaminated soil - Jianhua Qu; Rui Yu; Mengning Wang; Nanfang Wang; Fuxuan Bi; Hang Gao; Chang Qin; Yifan Wang; Ying Zhang (Chemical Engineering Journal, 2025)

Selective adsorptive separation of xylene isomers in vapor and liquid phases by nonporous adaptive crystals of leaning pillar[6]arenes - Yu-Xiang Sun; Susu Ren; Gengxin Wu; Xiang-Shuai Li; Haitao Wang; Jia-Rui Wu (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Jugular Vein Evans Blue Injection for Blood–Brain Barrier Assessment Following Hemorrhagic Stroke in a Mouse Model - Yu Zeng; Fang Wang; Rui Liu; Jian liu; Tao Xiong; Guodong Liu; Hao Yin; Guoqiang Han; Jian liu; Jiqin Zhang; Ying Tan (Translational Stroke Research, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

BDNF Alleviates Noise-Induced Cochlear Synaptopathy Through Inhibition of Autophagy - Fei Wang; Qianru Yu; Yangtuo Luo; Rui Guo; Liyuan Wu; Xinyu Song; Yang Li; Shuna Li; Ke Liu; Xuejun Jiang (Molecular Neurobiology, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

Identification and characterization of a new strain of Ictalurid herpesvirus 1 isolated from channel catfish in China - Fei Yu; Jiehua Xu; Sheng Yuan; Yi Yang; Siyang Song; Kai Hao; Rui Yuan; Yu Wang; Xiaohui Chen; Zhe Zhao (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Mechanistic insights into the impact of Lincomycin on microalgal-bacterial granular sludge in domestic wastewater treatment - Guihua Wang; Shujuan Meng; Bin Ji; Rui Wang; Min Liao; Xinyu Chang; Yu Liu; Meng Zhang (Journal of Water Process Engineering, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

Phosphogypsum aggregate-based high-permeability pervious concrete preparation: Towards low carbon and environmental friendly - Yike Chen; Xue Liu; Chiqiu Wu; Wei Lv; Kangning Liu; Siyu Wang; Jinyun Zhu; Xiangjun Chen; Rui Yu (Journal of Cleaner Production, 2025)

Microplastics impair black soldier fly bioconversion of pigeon manure: Physiological and transcriptomic insights - Zhimin Xu; Zheng Lin; Runtong Huang; Xueqing Chen; Lei Wang; Xingying Deng; Rui Du; Jiguang Gu; Yifan Wang; Renqiang Yu (International Biodeterioration & Biodegradation, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

Physicochemical characteristics, flavor profile, and microbial community of commercial traditional fermented chili pepper in Guizhou (Zao pepper) - Xijuan Zhang; Pei Gao; Qixing Jiang; Yongjun Wu; Shuhan Yang; Xiaojing Zhang; Rui Cao; Jing Wang; Min Jiang; Shaoquan Liu; Peipei Yu; Fang Yang; et al. (Food Bioscience, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Inactivation of Penicillium spp. in apple juice by pulsed light and the exploration of its mechanisms - Guolong Li; Saiqun Wang; Yu Li; Lu Cui; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Control, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Engineering B₄O₇2−-cross-linked double‑carbon layer separators for mitigating molecular shuttle in rechargeable small-molecule batteries - Xinyu Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Mingsheng Yang; Bei Wang; Haiping Yu; Mengxiao Li; Yuxin Hao; Zhihui Wang; Jingru Liu; Mingjun Hu; et al. (Chemical Engineering Journal, 2025)

Conduction of AgNPs with different surface charges in pine trees and their prevention and control of pine wood nematode disease - Shouhe Pan; Pengkun Yan; Rui Zhao; Fengyu Li; Lei Wang; Yinmin Wang; Ze Lv; Yingjian Ma; Meng Yu; Xinyu Guo; Yonggang Xia; Yong Xu; et al. (Chemical Engineering Journal, 2025)

“Zombie” cell drug delivery system: A novel strategy for the treatment of cancer and inflammation-related diseases - Zhouru Wang; Wenjing Yang; Danhua Liu; Peihong Lin; Rui Gao; Zhen Ma; Qiao Wang; Zhan Tang; Jie Fang; Wenying Yu (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

Significant enhancement of Acidithiobacillus ferrooxidans on the synergistic removal of As(III) by pyrite and red mud: Migration and transformation of As and Fe - Chenxu Wang; Maoxin Hong; Jun Wang; Rui Liao; Shitong Liu; Shichao Yu; Yang Liu; Baojun Yang; Guanzhou Qiu (Chemical Engineering Journal, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

PED-TRFIA: PEDV early on-site detection based on the time-resolved fluorescence ImmunoAssay - Bin Wang; Hongli Li; Rui Liang; Tingting Fu; Shusen Ji; Boya Li; Peichen Zhang; Haiyang Wu; Wenting Wang; Lianmei Bai; Xiuju Yu; Wei Hou; et al. (Analytica Chimica Acta, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Application and identification of monoclonal antibody targeting a novel epitope on p72 protein of African swine fever virus - Yu Dai; Xin Deng; Qi Wang; Ke Yang; Shuqing Yang; Xinran Li; Xinlei Liu; Yuanyuan Yang; Yu Gu; Yi Zheng; Rui Wu (Veterinary Microbiology, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Leaching salinity and mulching straws during freeze-thaw period enhance post-thawing cotton yield and quality by optimizing soil aggregates stability - Pengcheng Luo; Lu Zhao; Rui Chen; Pengpeng Chen; Yam Prasad Dhital; Haiqiang Li; Dongwang Wang; Juanjuan Yang; Yu Chen; Qinggang Liu; Zhenhua Wang (Soil and Tillage Research, 2025)

Mitigation of arsenic uptake and accumulation in rice grains by applying husk-derived silicon in a synergistic way: Evidence from pot and field trials - Xianghong LI; Xin WANG; Xionghui JI; Jingmin YANG; Yunping YU; Rui HUANG; Bo PENG; Baoshan XING (Pedosphere, 2025)

Physics-encoded deep learning for integrated modeling of watershed hydrology and reservoir operations - Bin Yu; Yi Zheng; Shaokun He; Rui Xiong; Chao Wang (Journal of Hydrology, 2025)

Life-long impacts of nanoplastics to rice plant (Oryza sativa L.): Decreased grain yield with perturbed metallome and soil microbiome - Hongxin Xie; Xuejia Wang; Liwei Cui; Rui Chen; Rui Zhao; Yang Yu; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2025)

Deciphering cadmium effects on biodegradation of triphenyl phosphate in sediments: Insights from molecular biology and computational chemistry - Dandan Li; Xiaoyu Wang; Chen Xie; Ziwu Fan; Rui Ding; Songqi Liu; Yu Chen; Kai Yu (Journal of Hazardous Materials, 2025)

Glyphosate threatens lizard adaptation to warming: Disruption to maternal effects - Simin Yu; Yue Zhang; Yufan Nie; Zikang Wang; Yuping Liu; Luyao Zhang; Rui Liu; Jinling Diao (Journal of Hazardous Materials, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Exploring the psychological impacts of air contamination: A cross-national study - Yu Hao; Shiyao Liu; Xueyu Rui; Xiaoxiao Hu; Lu Wang; Shen Wang; Guisen Zhang; Asyraf Afthanorhan; Zhi-Nan Lu (Journal of Environmental Management, 2025)

Virus communities rather than bacterial communities contribute more on nutrient pool in polluted aquatic environment - Qiaoling Yu; Xueqian Hu; Yuan Qian; Yu Wang; Chenwei Shi; Rui Qi; Petr Heděnec; Zhibiao Nan; Huan Li (Journal of Environmental Sciences, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Identification of potential natural compounds to relieve deoxynivalenol-induced intestinal damage based on bioinformatics and reverse network pharmacology - Rui Li; Kang Feng; Yu Du; Xuebin Fan; Yaqin Zhang; Chenli Wang; Jingdi Zhang; Sheraz Ahmad; Rafique Amna; Ci Liu; Ruiyan Niu; Zilong Sun (Food and Chemical Toxicology, 2025)

Modelling forest-atmosphere exchanges of carbon and water using an improved hydro-biogeochemical model in subtropical and temperate monsoon climates - Wei Zhang; Xunhua Zheng; Siqi Li; Shenghui Han; Chunyan Liu; Zhisheng Yao; Rui Wang; Kai Wang; Xiao Chen; Guirui Yu; Zhi Chen; Jiabing Wu; et al. (Ecological Modelling, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

Precursor ratio-modulated enzyme-mimicking ZIF-67 nanoflower array: A colorimetric “electronic tongue” for antioxidant monitoring - Peitong Yu; Boxu Wang; Huikai Lin; Weirong Zhou; Jiaxiong Li; Geyu Lu; Chunyan Sun; Rui Jin (Chemical Engineering Journal, 2025)

Bioinspired trilayer poly(ε-caprolactone) scaffolds with native-like structures and mechanical property for heart valve constructs - Zeping Zhang; Rizheng Han; Yueen Liu; Xinqi Yu; Guixue Wang; Yun Bai; Rui Yang; Tao Jin; Xing Zhang (Chemical Engineering Journal, 2025)

Catalytic phase transition of cobalt oxide enriched in mesoporous carbon polyhedrons for electrosorption of molybdate oxyanions - Yu-Jen Shih; Zhi-Lun Wu; Ming-Rui Wang; Chin-Pao Huang (Chemical Engineering Journal, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Contrasting leaf nutrient-hydraulic relationships between karst and non-karst forests - Chun-Yan Wan; Jun-Rui Yu; Zhong-Guo Li; Yong-Qiang Wang; Shi-Dan Zhu (Plant and Soil, 2025)

Microbial mediation of soil organic carbon fractions and its feedback to long-term climate change - Xinqi SiMa; Rui Fang; Zhenhua Yu; Yansheng Li; Xiaojing Hu; Haidong Gu; Caixian Tang; Judong Liu; Junjie Liu; Xiaobing Liu; Guanghua Wang; Ashley Franks; et al. (Plant and Soil, 2025)

Assessment of Thermal Vulnerability and Analysis of Influencing Factors in Urban Functional Areas of Foshan City, China - Xinyue Wang; Jun Yang; Rui Zhang; Jiaxing Xin; Wenbo Yu; Jiayi Ren; Xiangming Xiao (Chinese Geographical Science, 2025)

Parapedobacter flavus sp. nov., isolated from padding of fermentation bed - Rui Wang; Yan-Yan Zheng; Zi-Xuan Liu; Xuan Zhang; You-Jun Liao; Ya-Jing Yu; Ai-Hua Li (Antonie van Leeuwenhoek, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Unveiling anomalies in visual processing regions in obsessive-compulsive disorder: evidence from gray matter volume and functional connectivity analyses - Rui Liu; Fengxia Zhang; Pengchong Wang; Jia Luo; Yue Liu; Kaiyin Huang; Xiangyun Yang; Aihong Yu; Zhanjiang Li (Brain Imaging and Behavior, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

SETD2 regulates oocytes in vitro maturation through histone methylation and maternal mRNA degradation in yak - Hui Zhang; Yangyang Pan; Meng Wang; Jinglei Wang; Jiaxin Huang; Rui Ma; Shanshan Yang; Wenbin Ma; Sijiu Yu; Yan Cui (Theriogenology, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Sesquiterpenoids isolated from the root bark of Lycium chinense - Xiao-xia Wang; Qian Liu; Ning Wang; Rui-li Zhang; Xiao Li; Peng-yu Zhuang; Hang Liu; Liang-dan Sun; Yang Jin (Phytochemistry, 2025)

GO-SELEX-enhanced dual-recognition sensor for highly specific detection of azamethiphos - Lingjun Geng; Jingcheng Huang; Haowei Dong; Haifang Wang; Rui Xu; Zhiping Yu; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Journal of Hazardous Materials, 2025)

Biochar-loaded iron oxide as a novel electrode for the electro-Fenton degradation of sulfaquinoxaline: Performance evaluation, mechanistic insights, and toxicity transformation - Xiaowen Li; Sufang Wang; Jierong Zheng; Xin Fan; Jilong Qin; Yu Yang; Aijuan Zhou; Rui Li; Houfen Li; Xingfa Li; Xiuping Yue (Journal of Environmental Management, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Anti-fouling array paper-based device for rapid and accurate discrimination of foodborne pathogens in real samples - Kuiyu Wang; Yayue Huang; Yu Wan; Wang Chen; Jianwei Liang; Liangke Gong; Zebao Rui; Tao Yang (Food Chemistry, 2025)

One-step forming strategy of highly stable Li4SiO4 for low-concentration CO2 capture - Yu Zhang; Shuo Chen; Shikun Wen; Jiaojiao Li; Rui Yang; Liang Huang; Junya Wang; Ping Ning; Qiang Wang (Chemical Engineering Journal, 2025)

Plant Elemental Homeostasis Enhances Species Performance and Community Functioning in Wetlands: Looking Beyond Nitrogen and Phosphorus - Zhenjun Zuo; Zhong Wang; Haocun Zhao; Peidong Zhao; Rui Qu; Dan Yu (Ecology Letters, 2025)
Understanding how species optimise and stabilise their elementome, namely stoichiometric homeostasis ( H ), is crucial for species adaptation in changing environments. Species can be stoichiometrically homeostatic to different degrees, and elemental homeostasis is related to species' nutrient economic strategies. Recent studies on N and P homeostasis have provided a framework linking plant fitness to ecosystem functioning. However, the mechanisms by which homeostasis of bioelements beyond N and P affects species performance and community functioning remain poorly understood, despite the well‐established physiological functions of these bioelements. Based on 16 bioelements of 84 plant species from 232 wetlands, we found that bioelements with higher concentrations were more homeostatic in plants. Besides P, we further proposed that higher H K , H Ca and H Na enhanced species biomass, dominance, stability and community biomass. Climate, nutrient supply, community elemental concentration and homeostasis coregulated community biomass of submerged plants. These findings expand the stoichiometric framework for predicting the adaptative mechanisms of plants and their communities to environmental changes.

A Cross-sectional Study on Age-Related Changes in Muscle Iron Deposition and Fat Infiltration: Associations with Grip Strength in a Healthy Adult Cohort - Yiping Zhang; Xifa Gao; Rui Yu; Dingzhe Zhang; Yu Wang; Jianhua Wang; Xiao Chen (Biological Trace Element Research, 2025)

Identification of key genes linking bisphenols exposure and breast cancer - Zhen Wang; Meng Cao; Tian Gao; Xinyue Xu; Weihua Yu; Jiangzheng Liu; Rui Liu; Xiaodi Zhang; Fei Li; Chunxu Hai (Toxicology, 2025)

Using open GPS trajectory data to quantify nature-based recreation at a national scale - Pei Wang; Zhicong Zhao; Ruijia Zhu; Hao Wang; Shaochong Xue; Yiwei Liu; Fangyi Wang; Yue Cao; Le Yu; Rui Yang (Resources, Conservation and Recycling, 2025)

Ligand-rich oxygen evolution electrocatalysts reconstructed from metal-organic frameworks for anion-exchange membrane water electrolysis - Shiqi Li; Weiwei Liu; Yi Shi; Tang Wang; Tianyang Liu; Xiang Xue; Rui Li; Man Qiao; Zhen-Yu Wu; Wang Zhang (Science Bulletin, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Au-modified Cu2O with CO-enriched active sites for tandem catalysis of CO2 deep-reduction to C2H4 - Ji-song Yan; Wei Qiu; Hao Liu; Qing-shan Wang; Ling-qi Yu; Sheng-hui Guo; Rui-tang Guo (Journal of Environmental Chemical Engineering, 2025)

SfM on-the-fly: A robust near real-time SfM for spatiotemporally disordered high-resolution imagery from multiple agents - Zongqian Zhan; Yifei Yu; Rui Xia; Wentian Gan; Hong Xie; Giulio Perda; Luca Morelli; Fabio Remondino; Xin Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Construction of linear causal-regulated and autocatalysis-driven DNA circuits for highly sensitive and specific detection of Salmonella Typhimurium - Xinru Ren; Weiqing Sun; Bowen Li; Yijing Xiao; Xudong Yue; Meili Yang; Qing-ao Pang; Rui Zhu; Zhiqiang Guo; Haiping Zhang; Yu Wang; Su Liu; et al. (Food Control, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

Mediation role of gut microbiota in the association between ambient fine particulate matter components and cardiovascular disease: Evidence from a China cohort - Shaokun Yang; Rui Yu; Fen Yang; Jiawei Li; Lele Wang; Gonghua Wu; Liling Chen; Tingting Yang; Zhuoma Duoji; Yanjiao Wang; Xufang Gao; Yuanyuan Liu (Environmental Research, 2025)

The impact of natural organic matter on the aggregation, dissolution and sedimentation of cadmium telluride quantum dots and their interacting mechanism - Jing Wang; Pengxiang Zhu; Meiyu Li; Rui Lu; Xinping Yu; Lezun Wang; Lining Zhao (Environmental Research, 2025)

Metabolic and ecological responses of denitrifying consortia to different carbon source strategies under fluctuating C/N conditions - Rui-Zhe Sun; Yuan Pan; Jun Wang; Tong Gao; Han-Qing Yu; Jin Wang (Environmental Research, 2025)

Determination of VOC transport parameters in artificial skin and the influence of temperature on permeability - Haimei Wang; Rui Zhang; Xueqiong He; Lihua Sun; Xuefei Yu; Jing Zhao; Shaodan Huang; Jianyin Xiong (Environmental Pollution, 2025)

Ionic liquid-grafted MXene composite polymer electrolytes for high-performance solid-state batteries - Zhi Qian; Zhao-Dong Qiu; Rui-Qing Wang; Mei-Tong Wei; An-Min Fei; Zhi-Yi Hu; Hemdan S.H. Mohamed; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2025)

Trithiocyanuric acid trilithium salt: A low-cost, high-energy, reduction-state organic cathode material based on disulfide bond - Housheng Gong; Han Yan; Rui Wang; Xiaotang Gan; Liang Huang; Zijun Hu; Tingting Yu; Lihan Liu; Zhiping Song (Chemical Engineering Journal, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Ensemble framework for multistep carbon emission prediction: an improved Bi-LSTM model based on the Bayesian optimization algorithm and two-stage decomposition - Qi Song; Yu-Long Bai; Rui Wang; Xiao-Xin Yue; Wen-Hui Liu (Stochastic Environmental Research and Risk Assessment, 2025)

Integrative transcriptomic and physiological analyses uncover mechanisms by which arbuscular mycorrhizal fungi mitigate salt stress in sugar beet - Zeyuan Cui; Xiaodong Li; Pingan Han; Rui Chen; Yinzhuang Dong; Gui Geng; Lihua Yu; Jiahui Liu; Yao Xu; Yuguang Wang (Mycorrhiza, 2025)

The Spatial–Temporal Characteristics of Wave Energy Resource Availability in the China Seas - Rui-Zhe Shen; Cheng-Tao Yi; Yu-Nuo Liu; Lei Wang; Kai Wu; Mu-Yu Chen; Chong-Wei Zheng (Journal of Marine Science and Engineering, 2025)
For coastal nations and regions, wave energy provides a localized energy solution, decreasing dependency on external energy sources and fostering the sustainable development of local economies. Effective wave height occurrence (EWHO) represents the availability of wave energy and is a crucial parameter for site selection for optimal wave energy. This paper systematically analyzes the distribution of EWHO in China seas areas using significant wave height (SWH) data in the fifth generation of ECMWF atmospheric reanalysis (ERA5) and key climate indices. Employing methods such as climate statistical analysis, linear regression, significance testing, and trend analysis, the study highlights the temporal and spatial distribution characteristics, variation trends, and correlations with climate indices of EWHO. This research aims to provide technical assistance and decision support for the development of wave energy at sea. The results indicate the following conclusions: (1) The high EWHO in the China seas is predominantly located in northern Nanhai, southern Donghai, and the eastern waters of the Philippine Islands. The EWHO is highest in winter. (2) The growth trend of EWHO is most notable in the sea area east of the line connecting the Ryukyu Islands, Taiwan, and the northeastern Philippines, peaking in spring and being relatively weak in winter. (3) The correlation between NINO3 and EWHO is most significant in Nanhai and the northeastern waters of the Philippines, peaking in February with correlation coefficients ranging from −0.30 to −0.50.

Climate change impacts on city-scale building energy performance based on GIS-informed urban building energy modelling - Meng Wang; Jingfeng Zhou; Yujing Liang; Hang Yu; Rui Jing (Sustainable Cities and Society, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Multi-omics analysis reveals the role of L-Glutamate in regulating cold tolerance of postharvest prune fruit - Yuanyuan Hou; Wanyu Yan; Rui Deng; Jiayi Wang; Yu Wang; Liang Wang; Jun Xing; Peng Jin; Yating Zhao (Postharvest Biology and Technology, 2025)

Holocene coral reef carbonate REY geochemistry during the neomorphism from aragonite to calcite: A case study in the South China Sea - Wei Jiang; Yuwen Xiao; Kefu Yu; Rui Wang; Shendong Xu; Ning Guo; Tingwu Gu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Combining the bridging effect of tannic acid and solution activation for improving the lithium/magnesium separation performance of nanofiltration membrane - Tian Wang; Yajiao Long; Rui Yu; Yanqi Gan; Haonan Zhang; Jiahe Li; Mengqi Shi (Desalination, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Antibacterial conductive hydrogels with freeze-directed microstructures reinforced by polyaniline-encapsulated bacterial cellulose for flexible sensors - Feihong Hu; Dehai Yu; Baoting Dong; Xi Gong; Zhiyang Li; Rui Zhao; Qiang Wang; Guodong Li; Huili Wang; Wenxia Liu; Fengshan Zhang; Zhixin Chen; et al. (Chemical Engineering Journal, 2025)

Recent advances and future prospects of wearable sensors based on nanomaterial sensing mechanisms for biosafety monitoring - Xiaoyu Yu; Hui Li; Junwen Wang; Xin Zhang; Rui Jiao; Yuwei Ren; Danfeng Zhang; Na Ling; Yingwang Ye (Chemical Engineering Journal, 2025)

Antioxidant and immunomodulator nanoengineered probiotics for synergistic therapy of inflammatory bowel disease - Pandi Peng; Rui Ding; Junru Wang; Luofeng Yu; Yuxin Guo; Pengyu Chen; Tao Feng; Peng Li (Chemical Engineering Journal, 2025)

Fabrication of MXene/MOF composite separators for high performance lithium-sulfur batteries - Yinchuan Wang; Rui Niu; Liyi Chen; Yu Yang; Haizhou Yu; Xiaoyan Qiu (Chemical Engineering Journal, 2025)

Bacterial cellulose-based Pickering emulsions reinforced with silver and silica nanoparticles for advanced antibacterial and hydrophobic food packaging solutions - Qimin Chen; Fan Yang; Yalong Hou; Zhiyang Li; Di Yuan; Chao Liu; Feihong Hu; Rui Zhao; Huili Wang; Wenxia Liu; Fengshan Zhang; Qiang Wang; et al. (Carbohydrate Polymers, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Undrained permanent deformation characteristics of Yellow River silt under one-way cyclic loads - Yuke Wang; Hao Chen; Yujie Xue; Rui Jiang; Xiang Yu; Xiaoying Lin (Marine Georesources & Geotechnology, 2025)

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

Effect of 1-nitropyrene exposure on the biological behavior of trophoblast cells - Chuting Wang; Long Zhang; Daidi Gui; Wenjing Zou; Menglei Zhu; Yu Liu; Lei Hua; Changlian Li; Rui Ding (Reproductive Toxicology, 2025)

Graph-based pangenome provides insights into structural variations and genetic basis of metabolic traits in potato - Xiaoling Zhu; Rui Yang; Qiqi Liang; Yuye Yu; Tingting Wang; Li Meng; Ping Wang; Shaoyang Wang; Xianping Li; Qiongfen Yang; Huachun Guo; Qijun Sui; et al. (Molecular Plant, 2025)

A novel tannic acid/iron/hydrophilic polymer nanofiltration membrane for small organic pollutant/salt separation - Yajiao Long; Yanqi Gan; Xiong Yao; Tian Wang; Haonan Zhang; Rui Yu; Jiahe Li; Mengqi Shi (Journal of Environmental Chemical Engineering, 2025)

New insight into the role of bisphenol A on the anammox system: Oxidative stress and quorum sensing mechanisms - Yu Tian; Lingjie Liu; Chunsheng Qiu; Dong Wang; Rui Zhang; Yanmeng Bi; Shaopo Wang; Bo Zhang (Journal of Environmental Chemical Engineering, 2025)

Biochar-supported Fe₃O₄ nanoparticles affects bacterial community diversity and phosphorus speciation transformation during pig manure aerobic composting by generating hydroxyl radicals and hydrogen peroxide - Ning Yuan; Kang Wang; Jia Zhou; Nana Luo; Rui Yu (Journal of Environmental Chemical Engineering, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Co-culture fermentation of Debaryomyces hansenii and Bacillus atrophaeus alleviates quality deterioration of litchi fruit by ameliorating microbial community diversity and composition - Zhen Li; Yu Wang; Rui Li; Yuxin Hu; Xin Wang; Wen Li; Yuanzhi Shao (Food Microbiology, 2025)

Gridemis V2.0: A highly integrated algorithm scheme for high-resolution and multi-component allocation of emission inventories used in air quality models - Chuanda Wang; Wenjiao Duan; Shuiyuan Cheng; Xiaosong Hou; Junfeng Zhang; Yu Wang; Hanyu Zhang; Kai Wang; Rui Liu (Environmental Modelling & Software, 2025)

Amylopectin-enhanced MXene/gallium hydrogels: High-performance flexible conductive materials for multifunctional sensing, EMI shielding, and energy storage applications - Feihong Hu; Dehai Yu; Xi Gong; Zhiyang Li; Rui Zhao; Qiang Wang; Fengshan Zhang; Guodong Li; Huili Wang; Wenxia Liu; Yingjie Zhao; Huihui Li (Chemical Engineering Journal, 2025)

Iron-carbon amendment enhanced pollutant removal and greenhouse gas reduction in constructed wetlands under PFBA stress - Jiaqing Tao; Xiaoying Zheng; Chao Zhou; Zhilin Zhao; Tianxing Hu; Yi Fan; Yu Tang; Rui Wang; Tao Lin (Chemical Engineering Journal, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

An alternative ignition agent concept based on ionic integrated energetic oxidant - Xiaoxia Li; Peng Ren; Rui Wu; Yu Wang; Peng Deng; Kehua Han; Yu Shang; Shaoli Chen; Weixiong Zhang (Chemical Engineering Journal, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Swertiamarin relieves radiation-induced intestinal injury by limiting DNA damage - Zhe Zhao; Dan He; Jinyu Wang; Yu Xiao; Lixin Gong; Can Tang; Haibo Peng; Xuemei Qiu; Rui Liu; Tao Zhang; Jingyi Li (Molecular and Cellular Biochemistry, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Characterization of the gut microbiota in drug abuse: prediction, prevention, and personalized medicine to benefit affected populations - Xin Wang; Ya-Jie Yu; Cai Liao; Xiao-Ru Liu; Rui Yu; Yun Wang (EPMA Journal, 2025)

Centrifuge test study on the influence mechanism of anchor cable installation on the seismic response of pile‒anchor structures - Yu Wang; Tong Zheng; Rui Sun; Qiangqiang Sun; Xiao Long; Hongshuai Liu; Wenhao Qi (Soil Dynamics and Earthquake Engineering, 2025)

Fossil wood of Pinus from the Pliocene of western Yunnan, China and its palaeoclimatic implications - Zhi-Hui Song; Zhuo-Er Wang; Rui Cao; Zhao-Shuai Wang; Huai Wang; Gui-Hua Chen; Jing-Yu Wu (Review of Palaeobotany and Palynology, 2025)

Transcriptome profiling in peanut (Arachis hypogaea) in response to biotic stress produce by Bacillus amyloliquefaciens TA-1 - Wang Chen; Taswar Ahsan; Di Han; Wen-Rui Wang; Si-Tong Du; Chao-Qun Zang; Yu-Qian Huang; Ejaz Hussain Siddiqi (Plant Gene, 2025)

Molecular identification of three cytochrome P450 genes and their potential roles in insecticides tolerance in Grapholita molesta (Busck) - Hui Han; Ming-Gao Li; Kai-Yang Xing; Qi Wang; Jun Hu; Zhi-Guo Zhao; Qin Yu; Rui-Yan Ma; Ling-Ling Gao; Yan-Qiong Guo (Pesticide Biochemistry and Physiology, 2025)

Numerical and experimental studies on the hydrodynamic performance of a composite cylindrical perforated-wall caisson breakwater - Zi-bo Xia; Xin-yu Wang; Xiao Liu; Rui-jia Jin; Bao-lei Geng; Yong Liu (Ocean Engineering, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Occurrences of heavy metal in breast milk in China: Results of the third national breast milk survey - Rui Wang; Jiangkun Yu; Dawei Chen; Jingguang Li; Kemin Qi; Lan Ma; Bing Lyu; Xiaohong Shang; Yunfeng Zhao (Journal of Hazardous Materials, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

Performance of electro-assisted ecological floating bed in antibiotics and conventional pollutants degradation: Mechanisms and microbial response - Liangjing Zhang; Yan Luo; Shucong Lv; Yunlong Liu; Rui Wang; Yu Wang; Kuixuan Lin; Lusan Liu (Journal of Environmental Management, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Microbial community structure and water quality performance in local scrubber reclaim system for water reclamation of the semiconductor industry: A case study of a semiconductor plant in Beijing - Yu-Di Li; Yin-Hu Wu; Hao-Bin Wang; Rui-Ning Wang; Pei-Hua Li; Bang-Hao Huang; Hong-Ying Hu (Environmental Research, 2025)

Migration and distribution of thallium related with lead-zinc smelting enterprises from raw materials to soil: In-situ insight using diffusive gradients in thin-films - Wenhao Wang; Siwei Deng; Jiang Yu; Yi Wu; Wenjuan Feng; Qin Fan; Rui Zhou; Peirou Li; Wei Deng; Zhi Huang; Jie Yu; Weiwei Zhu (Environmental Pollution, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Coplanar two-dimensional Cu-MOF with dual-Cu sites for electrocatalytic CO2 reduction to C2H4 - Yu-Peng Han; Zi-Rui Wang; Ya-Yu Yan; Qiao-Hong Li; Ping Shao; Hai-Xia Zhang; Li-Li Han; Fei Wang; Jian Zhang (Chemical Engineering Journal, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

The impact of urban morphology on land surface temperature under seasonal and diurnal variations: Marginal and interaction effects - Zi Wang; Rui Zhou; Yang Yu (Building and Environment, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

2D Laplace-Fourier domain acoustic wave equation modeling with an optimal finite-difference method - Jing-Yu Wang; Na Fan; Xue-Fei Chen; Shou-Rui Zhong; Bo-Yu Li; Dan Li; Gang Zhao (Applied Geophysics, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Analysis of the city-scale wind environment and detection of ventilation corridors in high-density metropolitan areas based on CFD method - Rui Liu; Yuxiang Wang; Yu Zhang; Zhixing Peng; Hankai Chen; Xiang Li; Hang Li; Weiyue Li (Urban Climate, 2025)

Long-term warming offsets the beneficial effect of elevated CO2 on mineral associated organic carbon in Mollisols - Xinqi SiMa; Yansheng Li; Zhenhua Yu; Haidong Gu; Junjie Liu; Judong Liu; Rui Fang; Xiaojing Hu; Xiaobing Liu; Guanghua Wang; Caixian Tang; Ashley Franks; et al. (Science of The Total Environment, 2025)

Two new phenolic glycosides from the rhizomes of Paris yunnanensis - Yu-Rui Xie; Shan-Shan Ling; Yan-Xi Li; Mei-Ru Wang; Hai-Yang Liu (Phytochemistry Letters, 2025)

Alkaloids from Dendrobium nobile and their anti-inflammatory activities - Zao-Yu Xu; Chao-Fan Wang; Wen Li; Nan Fu; Rui Zhan (Phytochemistry Letters, 2025)

Experimental study on decarburization process and emission of multi-air-staged and self-sustainable preheating combustion of coal gasification fine slag: From lab-scale study to full-scale demonstration - Zhaochen Shi; Rui Li; Gaofeng Dai; Jiaye Zhang; Yongqiang Chen; Wei Yu; Yili Zhang; Xuebin Wang (Fuel, 2025)

A novel approach of in-cylinder NOx control by inner selective non-catalytic reduction effect for high-pressure direct-injection ammonia engine - Rui Yang; Zongyu Yue; Shouzhen Zhang; Zining Yu; Hu Wang; Haifeng Liu; Mingfa Yao (Fuel, 2025)

Three-dimensional MOFs confined Anderson-type POMs clusters—Templated fabrication of porous Co-NiMo/Cr2O3 catalyst with superior NH3-SCR catalytic activity - Yu Zhang; Rui Wang; Jingcai Chang; Min Yue; Yong Cai (Fuel, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Regulation of multilayer long crystalline MoS2 by NiO-modified Al2O3 for improved hydrodesulfurization of COS - Yubiao Li; Yu Liu; Xueqian Wang; Yixing Ma; Ping Ning; Langlang Wang; Xiang Li; Rui Cao (Environmental Research, 2025)

Deciphering the mineral code of urinary stones: A first look at zinc isotopes - Ziyang Ding; Guilin Han; Yu Tian; Rui Qu; Jinke Liu; Di Wang; Ye Zhao (Environmental Pollution, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Uncovering the mechanisms of diosmin in treating obesity-related kidney injury based on network pharmacology, molecular docking, and in vitro validation - Jun-Xing Zhu; Fan Chu; Wen-Man Zhao; Rui Shi; Zhi-Juan Wang; Xun-Liang Li; Yu-Yu Zhu; De-Guang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Metabolic and neurodevelopmental effects of the environmental endocrine disruptor di-2-ethylhexyl phthalate: a review - Weiwei Wang; Xiaolei Liu; Yu Ding; Rui Bu; Wei Miao; Jianhong Han; Tianhao Bao (Environmental Chemistry Letters, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

A new anti-inflammatory thujane monoterpenoid glycoside ester from Pittosporum heterophyllum Franch - Jia-Qi Ding; Sheng-Nan Guan; Yu-Feng Zhang; Zhao-Xuan Wang; Wei-Zhen Kong; Jun-Rui Ren; Xiu-Yun Zhang (Natural Product Research, 2025)

Integrating network pharmacology and experimental verification to reveal the ferroptosis-associated mechanism of Changpu-Yizhi-Wan in the treatment of Alzheimer's disease - Rui Xiong; Hengxu Liu; Shipeng Zhang; Lu Wang; Lu Liu; Sicen Pan; Yu Zhang; Fengying Zhu; Yao Liu; Xiaodan Lai (Metabolic Brain Disease, 2025)

Three new isoquinoline alkaloids from the fermentation of Aspergillus sp. 0338 and their anti-MRSA activities - Min Yang; Miao Dong; Qing-Yang Wu; Shui Yao; Gui Pu; Yue-Yu Ma; Rui-Feng Xiong; Qiu-Fen Hu; Fang Wang; Yin-Ke Li (Natural Product Research, 2025)

The reverse-reduction effect of dissolved organic matter on the degradation of micropollutants induced by halogen radicals (Cl2•- and Br2•-) - Shuangshuang Cheng; Rui Cui; Yangjian Zhou; Yu Lei; Ni Wang; Yanheng Pan; Xin Yang (Water Research, 2025)

How does shared mobility impact metro-based urban commercial travel accessibility and Equity? - Rui Zhou; Yang Yu; Zi Wang; Luheng Ke; Jin Zhao (Transportation Research Part D: Transport and Environment, 2025)

Revealing the impact of urban spatial morphology on land surface temperature in plain and plateau cities using explainable machine learning - Zi Wang; Rui Zhou; Jin Rui; Yang Yu (Sustainable Cities and Society, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Heat-resistant boron Carbonitride with nitrogen-vacancies and oxygen-doping for efficient tetracycline removal: Adsorption characteristics, mechanism and regeneration - Xu-Dong Miao; Rui-Xiang Zhang; Wen-Tao Li; Qian Wang; Yu-Han Cai; Yong Guo; Ai-Min Li (Journal of Water Process Engineering, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Aged garlic oligosaccharides modulate host metabolism and gut microbiota to alleviate high-fat and high-cholesterol diet-induced atherosclerosis in ApoE−/− mice - Xiaomin Wang; Jianglu Cui; Ziyao Gu; Lili Guo; Rui Liu; Yu Guo; Nan Qin; Yukun Yang (Food Chemistry, 2025)

Effects of chitosan/eugenol-loaded IRMOF-3 nanoparticles composite films on reactive oxygen species metabolism and microbial community dynamics in postharvest strawberries - Yuyue Qin; Hongda Yu; Kejun Chen; Rui Cui; Jianxin Cao; Zhengxuan Wang; Zhi-Hong Zhang; Thanapop Soteyome (Food Bioscience, 2025)

Poly-γ-glutamic acid chelates chromium (III) and copper (II), alleviating their toxicity in cucumber and affecting rhizosphere bacterial community assembly - Chaoyang Chen; Wenhui Yan; Yu Chen; Sijie Liu; Chuanjiang Nong; Liang Sun; Rui Wang; Hong Xu; Peng Lei; Yian Gu (Environmental Pollution, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

Evaluation of the shear stiffness and load redistribution of framed structures affected by tunnelling - Jingmin Xu; Zehui Yu; Rui Chen; Tao Xu; Churong Chen; Ziqi Wang (Computers and Geotechnics, 2025)

Robust and porous cationic polymeric network nanofiber membrane with high alkaline stability for efficient 99TcO4−/ReO4− removal - Minsi Shi; Dingyang Chen; Xinyue Zhao; Zixu Ren; Guangli Yu; Ce Wang; Rui Zhao; Guangshan Zhu (Chemical Engineering Journal, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Regulation of oxygen vacancy by in-situ piezoelectric synthesized BiVO4 to induce spin polarization for boosting the piezo-photocatalytic activity - Ying Cheng; Tao Yu; Xuefei Lei; Biao Wang; Wenning Mu; Xuanwen Liu; Rui Guo (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Eliminating bacterial endotoxins and associated inhalation hazards in reclaimed water via ultraviolet/ferrate combination disinfection - Muhan Sun; Xiaoxu Jiang; Rui Liu; Deqin Kong; Hao Wu; Zhao Wang; Gang Zheng; Chongmiao Zhang; Weihua Yu (Chemical Engineering Journal, 2025)

In-situ constructing 3D nanocarbon conduction conformal network on silicon anodes for high-performance sulfide-based all-solid-state batteries - Rui Huang; Ruilong Li; Shaobo Li; Wen Yang; Yu Bai; Zhenhua Wang; Kening Sun (Chemical Engineering Journal, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Portable paper-based microfluidic devices with Cu1-xAgxS NPs modification for multiplex intelligent visualized detection of adrenaline and glucose simultaneously - Huan Wang; Lihua Dong; Gina Ma; Shuang Qiu; Guiye Shan; Lijia Zhao; Yu Sun; Anni Cui; Rui Zhang; Xiaojie Liu (Analytica Chimica Acta, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Roseobacter weihaiensis sp. nov., a cellulose-degrading bacterium isolated from intestinal content of Nipponacmea schrenckii collected from golden beach in Weihai, China - Yu-Rui Li; Ming-Jing Zhang; Yan-Jun Yi; Xiao-Chen Wang; Dong-Mei San; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2025)